REPRESENTATION OF ANXIETY IN THE THING AROUND YOUR NECK BY C. N. ADICHIE (A STUDY OF TRANSITIVITY) - Avissa Chaerinda Yahya; Deli Nirmala (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2021)
This study discusses a short story entitled The Thing Around Your Neck by Chimamanda Ngozi Adichie. The purpose of writing this study started from the curiosity of the researcher to find out the anxiety that is reflected in the contents of the short story. As stated in the title of the story, The Thing Around Your Neck, the word thing is described as a symbol of anxiety experienced by the narrator, Akunna. Akunna is one of the main characters in the short story. She is described as a Nigerian-women who is traumatized by her life in America, exhibiting many psychological problems in the form of anxiety. Akunna shows worry, loneliness, helplessness in all life situations that she has to live in. The aims of this study are: 1) to conduct a transitivity analysis to find out how much anxiety is depicted in the story; 2) to explain the anxiety that occurs in the story. The researcher applies descriptive qualitative methods in conducting research and used a non-participant observation method as the data collection method. The data analysis that the researcher used in this study is referential technique. The results of the study show that: 1) there are 5 transitivity processes that represent anxiety in the story, 2) Akunnas' anxiety is caused by the helplessness and stereotypes she receives from the people around her, both Africans and Americans. Keywords: Systemic Functional Linguistics; Anxiety; Short Story; Transitivity